Que saberes anunciam profissionais da educação Infantil? Um estudo em contexto de uma formação in lócus - Martins, Andressa de Oliveira (2017)
The present research was produced in the University Extension Project. For that, a problem was elaborated and organized in form of a question: what are the knowledges of Early Childhood Education professionals revealed in the University Extension Project? Under this questioning, this dissertation was aimed to understand what knowledges of Early Childhood Education professionals are shown in the Activity Extension. We also sought to raise and describe aspects related to the participation (training) of these professionals, in this project, and to identify and analyze the knowledge revealed in the context of this university extension action. From a qualitative perspective, this research was carried out by means of a bibliographical survey, followed by the theoretical support of authors such as Kramer, Nóvoa, Tardif, Imbernón, Machado, Formosinho, Rosseti-Ferreira and Kishimoto, among others to gain a higher knowledge of the subject. We built the theoretical referential around themes such as: teacher training, Early Childhood Education and knowledges. The field research had as instrument for data collection the focal group, with recording of footage and transcription of images and audio. It was carried out with 16 Early Childhood Education teachers - working in day-care centers (13 teachers, 1 head mistress, 1 physical education teacher, 1 lunch lady), participants in the VEREDAS Project. Data analysis was performed through content analysis. The research data were organized into two categories: "Being in the University Extension Project" and "Knowledges of professionals of Early Childhood Education". The results of the research revealed specific knowledge to perform with infants and young children and also the importance of continuing training, with emphasis on the training process that takes place within the University Extension Project. The approach between universities, day-care centers and pre-schools, through this Project, enabled the formation in context of this group of professionals in Early Childhood Education, since the results showed that this extension activity was constituted as a space for collaboration, dialogue, reflection , learning, exchange of knowledge and experiences, as well as a space for professional affirmation and recognition of knowledge.